Distribution and ecological requirements of ostracods (Crustacea) at high altitudinal ranges in Northeastern Van (Turkey) - (:unkn) unknown (EDP SCIENCES S A, 2012)
To understand ostracod distribution and ecology at high altitudes (1659-2889 m 78 different aquatic sites located in the city of Van were sampled during summer of 2009. A total of 29 ostracod species were recorded in 57 sites. Among the species, Trajancypris Iaevis (G.W. Muller 1900), is a new report for the Turkish ostracod fauna. First axis of Canonical Correspondence Analysis (CCA) explained about 68% of the relationships between the 13 most abundant species and environmental variables. Four variables (redox potential, habitat type, pH and electrical conductivity) had the greatest effect on species composition (P < 0.01). Twenty-six species encountered from 38 stations were restricted between 1659 and 1750 m a.s.l. Above 1750 m a.s.l., the numbers of species were not significantly affected by altitude (P > 0.05). Three species (Heterocypris incongruens (Ramdohr, 1808), Hyocypris bradyi Sars, 1890 and Potamocypris villosa (Jurine, 1820)) occurred extensively from 1650 to 2350 m a.s.l. Spearman rank correlation revealed a negative relationship between Limnocythere inopinata (Baird, 1843) and altitude (r = -0.894, P = 0.05). while two species (I. MOO and Prionocypris zenkeri (Chyzer and Toth, 1858)) had a positive correlation to dissolved oxygen (P = 0.05). There was a significantly negative relationship between Hyocypris inermis Kaufmann, 1900 and electrical conductivity, and H. Mcongruens showed a significant correlation to station type. Five groups of species were determined by UPGMA analysis. Species in each cluster were grouped according to ecological conditions suitable for them. Results revealed that species ecological tolerances and optimum levels can be species-specific but species with cosmopolitan distributions tend to have high tolerance ranges to different variables, including altitudinal changes.
Keywords: Ostracod diversity; high altitude; ecology; optimum and tolerance; distribution; cosmopolitan; BOLU REGION; LAKE; SPRINGS; EASTERN; HABITATS; NEVADA